Economic effects of raspberry production on the family farm - Nataša Kljajić; Jonel Subić (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The paper presents the results of research related to raspberries production in the Republic of Serbia with a focus on the Zlatibor district and selected agricultural holding located in the area of the municipality of Arilje. The research was conducted in accordance with the real data from practice. The pedo-micro-climatic conditions in this area are suitable for raspberries cultivation being within the optimal values for its production. Water resources are also adequate for irrigation applications during the growing season. Research has shown that the total costs of production on the selected (representative) agricultural holding amount to exteuro8,198.5/ha when the irrigation and manual harvesting of raspberries are applied. The annual financial result (profit) is favorable and amounts to exteuro27,649.9/ha. The economic and financial results of the research showed that raspberries production is extremely profitable in this part of Serbia.
Keywords: Q0; Q10; Q12; 330; raspberries; production; economic analysis; costs; profit